A experiência da participação em conselhos de políticas públicas: uma análise psicossocial - Santos, Jean Fernando dos (2015)
Participation in Municipal Councils is a historic achievement of the social movements and organizations that fought for democratization of the country. With its forecast in the Federal Constitution of 1988, sought to through the institutionalization of these spaces through public policies, people's involvement in building democratic advances still needed for the universalization of social rights and the socialization of politics. After 27 years of its forecast, despite a significant expansion of these and public policy, there are several criticisms on how effectively is the participation in these spaces. From the Socio-Historical Psychology, this study aimed to make a psychosocial analysis in order to understand the subjective dimension of participation in a Municipal Council. For that we used participant observation in regular and special meetings of the board focused on positions/meanings/actions that serve as reference to the directors with respect to participatory experience. It was noted that the reference to participation is in line with the perspective of managerial State, that reduces a practice of de-politicized management and against the process of struggle for universal rights. In our analysis, we point out that this hidden understanding power relations and also their own genesis in the relations of the structure/superstructure of capitalist transformation processes in Brazil. The denaturalization of the subject involved, to identify it as a historical subject, allows to identify processes that hide authoritarianism under a notion of bourgeois democracy. Finally, understanding the contradictions within civil society, it is concluded that the notion of participation on the boards for universal rights can be strategically promoted in that it is effective socialization policy with effective promotion of the participation of service users